Creative Storytelling: Its Effectiveness in Enhancing the Listening Skills Among Grade 1 Learners - Acal, Marienel (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the effectiveness of creative storytelling in enhancing the listening skills of Grade 1 learners in the private elementary schools of Agoo, La Union during the school year 2025–2026, as basis for proposed intervention strategies. Anchored on learning theories related to multisensory learning, constructivism, dual coding, schema development, cognitive load, narrative engagement, metacognition, social learning, and affective language acquisition, the study employed a descriptive research design. Total enumeration was used, involving eleven Grade 1 teachers and four school administrators. Data were gathered through a validated questionnaire-checklist and analyzed using frequency counts, weighted means, rankings, and t-test at the 0.05 level of significance. Findings showed that the listening skills of Grade 1 learners during creative storytelling activities were rated satisfactory. Teachers perceived creative storytelling as highly effective, while school administrators rated it as moderately effective. Learner participation and the impact of creative storytelling on listening skills were both moderate. The major challenges encountered were poor discipline during storytelling sessions, short attention span, and limited parental support for storytelling activities at home. The study also found no significant difference between the perceptions of teachers and school administrators regarding the effectiveness and impact of creative storytelling. The study concluded that creative storytelling is relevant, useful, applicable, and efficient in enhancing learners’ listening skills, although implementation challenges must be addressed. It recommended the adoption of proposed intervention strategies, continued use of meaningful storytelling activities, close learner monitoring, and similar studies in other settings. The study supports SDG 4 – Quality Education and SDG 17 – Partnerships for the Goals by promoting learner-centered instruction and collaboration among teachers, administrators, parents, and schools. Its sustainability impact lies in strengthening educational and institutional practices for early literacy development.